Implementasi Kurikulum Pendidikan Agama Islam Pasca Bencana Alam : Studi Kasus Banjir Bandang di Bumiayu Brebes - Mu’tamaroh (An Nafi': Multidisciplinary Science, 2025)
This study examines the implementation of the Islamic Religious Education (PAI) curriculum in areas affected by natural disasters, specifically the flash floods in Bumiayu, Brebes. The study focuses on the adaptation of curriculum policies, PAI teacher strategies, and the learning challenges that emerged post-disaster. Using a qualitative case study approach, data was collected through analysis of documents, news reports, and previous research related to post-disaster education. The results indicate that the implementation of the PAI curriculum has undergone significant changes, particularly in the adjustment of core competencies, learning methods, and the integration of morality and spiritual resilience materials. PAI teachers play a crucial role in restoring students' psychosocial well-being through flexible, humanity-centered learning. This study emphasizes the urgency of reconstructing the PAI curriculum to be responsive to emergency situations, adaptive, and foster students' spiritual resilience.